Tarsicio de Azcona, OFMCap (Jesús Morrás Santamaría) - Echeverría, José Ángel (Huarte de San Juan. Geografía e Historia, 2014)
The author, after briefly outlining the biography of Tarsicio de Azcona, historian, whose research work has focused on the fifteenth and sixteenth centuries, especially in the reign of the Catholic Kings, offers the almost exhaustive cast of his bibliographical production, where highlights the biography of Queen Elizabeth. Besides, his studies have had as an outstanding object the Catholic pre-reform in Spain (mainly in the episcopate and religious orders), the conquest of Navarre (1512), the situation of the province of Gipuzkoa in the first decades of the sixteenth century, the founding of Capuchin province of Navarre-Cantabria and its friaries, including some of the province of Aragon, matrix province of the Navarre one (XVII century), and local studies on the Valley of Yerri and the village of Azcona, birthplace of the author.